A test for rate‐coupling of trophic and cranial evolutionary dynamics in New World bats. (24th February 2021) - Shi, Jeff J.; Westeen, Erin P.; Rabosky, Daniel L.
Abstract: Morphological evolution is often assumed to be causally related to underlying patterns of ecological trait evolution. However, few studies have directly tested whether evolutionary dynamics of—and major shifts in—ecological resource use are coupled with morphological shifts that may facilitate trophic innovation. Using diet and multivariate cranial (microCT) data, we tested whether rates of trophic and cranial evolution are coupled in the radiation of New World bats. We developed a generalizable information‐theoretic method for describing evolutionary rate heterogeneity across large candidate sets of multirate evolutionary models, without relying on a single best‐fitting model. We found considerable variation in trophic evolutionary dynamics, in sharp contrast to a largely homogeneous cranial evolutionary process. This dichotomy is surprising given established functional associations between overall skull morphology and trophic ecology. We suggest that assigning discrete trophic states may underestimate trophic generalism and opportunism, and that this radiation could be characterized by labile crania and a homogeneous dynamic of generally high morphological rates. Overall, we discuss how trophic classifications could substantively impact our interpretation of how these dynamics covary in adaptive radiations.